Aplikasi Value Engineering pada Proyek Konstruksi (Studi Kasus: Proyek Pembangunan Gedung BPKP Yogyakarta) - Priyo, Mandiyo; Hermawan, Totok Dwi (Universitas Muhammadiyah Yogyakarta, 2010)
Construction of a building project or the others structures needs cost, so that the project can be realized. Before an owner continues the project to the design or construction steps, the cost must be provided. The cost often becomes a problem because amount of the cost is limited to realize a construction project. The objective of this study is to select good alternative materials without declining the quality and function of the building as well as to find the value of cost efficiency on the Project of the BPK’s Office Building Construction of Yogyakarta by Value Engineering method. Value Engineering is a management thenique with systematic approach for finding the balance among cost, reliability, and performance of a product or a project. The study on the Project of the BPKP’s Office Building Construction of Yogyakarta was done on the structure work only, namely: plate, beam, column and sloof works with giving alternative materials for getting the best alternative by work plan of Value Engineering. The Value Engineering method was applied on structure components by systematic and creative approach trough work plan of Value Engineering using the following steps: an information, functional analysis, creative, development, writing and presentation steps. All steps were done continuesly and the result was expected giving efficiency from the previous design. From the application of Value Engineering, it is concluded that the cost efficiency is about 2.53% of total cost of structure work by application.